Hormone measurement in social neuroendocrinology: A comparison of immunoassay and mass spectrometry methods - Schultheiss, Oliver; Dlugash, Gelena; Mehta, Pranjal H. (Routledge international handbook of social neuroendocrinology, 2019)
CRIS-Team WoS Importer:2020-01-17

Monitoring of the dopamine D2 receptor agonists hordenine and N-methyltyramine during the brewing process and in commercial beer samples - Sommer, Thomas; Dlugash, Gelena; Hübner, Harald; Gmeiner, Peter; Pischetsrieder, Monika (Food Chemistry, 2019)
The phenethylamine alkaloid hordenine, present in germinated barley, was identified recently as a functionally selective dopamine D2 receptor agonist contributing potentially to the rewarding effects of drinking beer. Here, it was shown that the hordenine precursor N-methyltyramine binds with a similar affinity to the dopamine D2 receptor as hordenine (K-i 31.3 mu M) showing also selectivity towards the G protein-mediated pathway over the beta-arrestin pathway. Using a newly developed UHPLC-ESI-MS/MS method to monitor beer production, we demonstrated that hordenine and N-methyltyramine were released continuously from barley malt during mashing and were stable during fermentation and conditioning. The amounts released from different base malt types were in a similar range but tended to be higher from caramel malts. Hordenine and N-methyltyramine concentrations in 24 types of beer varied between 1.05-6.32 and 0.59-4.61 mg/L, respectively. Thus, the human uptake of the alkaloids during beer consumption is in the low milligram range.
Keywords: Beer; Brewing; Dopamine D2 receptor agonist; Fermentation; Hordenine; Mashing; N-Methyltyramine

Relationships of the Ulna-to-fibula Ratio to Baseline and Reactive Steroid Hormone Levels: An Exploratory Study - Köllner, Martin; Braun, Sinja; Schoettner, Hanna; Dlugash, Gelena; Bettac, Marlene; Steib, Simon (Adaptive Human Behavior and Physiology, 2022)
Objective Organizational hormone effects on the human brain and behavior are often retrospectively assessed via morphological markers of prenatal (e.g., 2D:4D digit ratio) or pubertal (e.g., facial width-to-height ratio, fWHR) hormone exposure. It has been argued that markers should relate to circulating hormones particularly in challenging, dominance/status-relevant situations. However, meta-analytic research indicates that fWHR, a frequently used pubertal marker, is neither reliably sex-dimorphic nor related to steroid hormones. This casts doubt on fWHR's validity for reflecting hormone levels. Ulna-to-fibula ratio (UFR), an alternative, long-bone-length-based pubertal marker, is sex-dimorphic and associated with dominance motivation. However, its hormonal associations were never tested before. We therefore explored UFR's relationships to baseline and reactive hormone levels. Methods We measured ulna and fibula length as well as shoulder/waist/hip circumference of 81 participants (49 women; after exclusions) via anthropometry. Salivary hormone levels (estradiol, testosterone) at baseline and after a gross-motor one-on-one balancing contest were measured via radioimmunoassay. Results We replicated UFR's dimorphism, unrelatedness to height, and correlations to other putative markers of organizational hormone effects. On an exploratory basis, we found UFR to be related to overall baseline testosterone and to competition-induced reactive surges in steroid hormones (estradiol, testosterone) overall and in women. Conclusions Our results hint at UFR's relationship to baseline testosterone and may indicate functional connections between outcomes of pubertal organizational hormone effects and contest-induced steroid reactivity. Pubertal organizational hormone effects may prepare the endocrine system for dominance and status contests. However, the small sample and the exploratory nature of our research demands replication.
CRIS-Team WoS Importer:2022-09-09

Suitability of saliva stimulants for valid assessment of steroid hormones via radioimmunoassay - Dlugash, Gelena; Schultheiss, Oliver (Psychoneuroendocrinology, 2021)
Salivary steroid measurement is a popular way to assess endocrine hormone levels, but efficient sample collection can be challenging because the use of stimulants can interfere with valid measurement. The aim of this study was therefore to identify a stimulant that can be used in assessment of the steroid hormones cortisol (C), testosterone (T), progesterone (P) and estradiol (E2) without impairing their quantification by radioimmunoassay. Study 1 and 2 explored the suitability of potential stimulants in comparison to unstimulated saliva collection. Study 3 tested stimulants under standardized conditions in water. Across all three studies, Parafilm® wax foil performed best and was therefore tested once more and validated as a saliva stimulant in Study 4. No significant differences between unstimulated saliva and Parafilm®-stimulated saliva could be found for any of the four hormones assayed. Therefore, Parafilm® appears to be a suitable saliva flow stimulant for assaying the salivary steroid hormones C, T, P and E2 by radioimmunoassay.
CRIS-Team Scopus Importer:2021-03-12
Keywords: Radioimmunoassay; Saliva stimulant; Steroid hormones